Pengaruh Penerapan Lembar Kerja Peserta Didik (LKPD) Berbasis Lingkungan Terhadap Hasil Belajar Siswa di SMP Yakhalusti Pontianak - yuniwarsih resi; Rika Anggela; Ivan Veriansyah (LPD IKIP PGRI Pontianak, 2023)
learning media can be used as an innovation to improve scholar gaining knowledge of outcomes, mainly since the surroundings is the location closest to students' every day activities. The motive of this examine changed into to at least one) discover the learning results of manipulate class students with the software of environment-primarily based scholar Worksheets (LKPD) to studying outcomes 2) find out the getting to know effects of experimental magnificence students without the utility of environment-based student Worksheets (LKPD) to scholar getting to know results. three) determine the impact of the application of environment-based pupil Worksheets (LKPD) on pupil results at SMP Yakhalusti Pontianak. The technique used is an experiment with a quasi-experimental shape and a two group post check best design. The results confirmed: 1) the mastering results of college students who had been taught by way of gaining knowledge of the software of scholar worksheets (LKPD) primarily based on the environment were labeled as proper, namely seventy seven.56. 2) the learning results of students who are taught with out gaining knowledge of the application of environment-based totally student worksheets (LKPD) are categorized as right, specifically 71.eighty four. 3) based totally on the records above, the Cohen'd result is 1.26. So it can be concluded that for the impact size there may be an influence between studying the utility of environment-based pupil worksheets (LKPD) and mastering outcomes with a end result of 62.2%, these consequences also can be prompted with the aid of numerous other types of elements